The Comparison of Obesity and Physical Activity Levels of Private and Public Secondary School Children - Emine Kaymaz; Özcan Saygın; Gönül Babayıgıt Irez (Selcuk University, 2018)
This study was conducted to compare of obesity and physical activity level of secondary school children in private school and public schools. Total 697 students consisting of 342 girls and 355 boys participated voluntarily in this study. Physical Activity Questionnaire for children was used to determine physical activity levels and height-weight measurement was performed to determine body mass index. It was found that the overweight ratio was %9.49 of girls in public secondary schools while the ratio of overweight girls was %18.40 in private schools. The boys' over weight ratios were %23.58 in public schools while the ratio of overweight was % 27.5 in private schools. Significant differences were found between BMI and weight parameters of private and public secondary schools. No difference was found in physical activity levels of private and public school student. Moreover, there was no correlation between physical activity levels and BMI variables of students in private and public school according to gender. The physical activity levels of secondary school children' should be increased.